Mobile innovation on Caribbean islands - Eliasz, Toni; Doerr, Rick (Technical Centre for Agricultural and Rural Cooperation, 2013)
The Caribbean Mobile Innovation Project, launched by info Dev, aims to help mobile app innovators in the region bring their mobile apps, services and content to the market and build growth-oriented startups into successful enterprises.